Criminalization of torture in the Chilean legal system in the light of the International Human Rights Law: status and challenges - González Ampuero, Felipe (Revista Tribuna Internacional, 2014)
The present article aims to determine the degree in which the obligation to criminalize torture, which appears explicitly in international treaties ratified by the Chilean state, has been fulfilled. With that purpose, for each one of those international instruments the definition of the concept of torture -and the content of the obligation to criminalize it- is revised, so we can then analyze how much does the domestic definition complies with the demands of those treaties. Lastly, the differences between the international treaties themselves are also analyzed in relation with the standards of criminalization, with the purpose of highlighting some considerations that should be had in mind at the time of changing the domestic definition of torture, as to fully comply with the obligation of criminalization.